Comparative Evaluation of Postoperative Pain Following Different Irrigation Activation Techniques in Single-Visit Endodontics (Academia Journal of Medicine, 2026)
Postoperative pain following endodontic treatment remains a significant clinical concern  influenced by irrigation techniques. This study aimed to evaluate and compare postoperative  pain following different irrigation activation methods in single-visit endodontics. A total of  90 patients were divided into three groups based on the irrigation technique used: manual  dynamic agitation, passive ultrasonic  irrigation, and laser-activated irrigation, and pain was  assessed at different time intervals using a numerical rating scale. The results  demonstrated   variations in postoperative pain among the groups, with advanced activation techniques  showing better pain   reduction   compared to   conventional methods. It can be concluded that  irrigation activation techniques play  a significant  role in minimizing  postoperative pain,  and  their  appropriate selection  can improve  patient  comfort and  clinical  outcomes. Advancement of Knowledge This study provides comparative clinical evidence on the effect of different irrigation  activation techniques on postoperative pain following single-visit endodontic treatment. It  demonstrates that advanced activation methods, such as passive ultrasonic irrigation and  laser-activated irrigation, are more effective in reducing postoperative pain compared to  conventional approaches.The findings highlight the role of improved irrigant penetration  and reduced apical extrusion in minimizing periapical inflammation and patient discomfort.  Additionally, this study emphasizes the importance of selecting appropriate irrigation  techniques as a key factor in enhancing clinical outcomes and patient satisfaction in  endodontic therapy.
Keywords: Postop erative pain; Endodontics; Irrigation activation; Passive ultrasonic irrigation; Laser-activated irrigation; Manual dynamic agitation; Single-visit root canal treatment